DNA methylation and immune regulation in osteoporosis: emerging epigenetic targets for drug discovery - Yang, Yingli; Yao, Yao; Cai, Xiaoyu; Tao, Yaqi; Zhuge, Zhengbing; Zhou, Jianhong; Zheng, Caihong (Frontiers in Pharmacology, 2025)
Osteoporosis (OP) is a complex skeletal disease characterized by the disruption of bone homeostasis, with immune dysregulation identified as a significant pathogenic cause. The interaction between immune cells and bone cells within the bone marrow microenvironment affects osteoclast (OC) activation and osteoblast (OB) function through cytokine networks, including RANKL/OPG and Wnt signaling. Aberrant DNA methylation, a significant epigenetic change, influences osteoporosis by regulating the expression of genes associated with bone metabolism (e.g., RUNX2, NFATc1, SOST) and modifying immune cell activities, thereby facilitating inflammatory bone loss. Increased DNA methyltransferase (DNMT) activity has been associated with osteoimmune dysregulation, oxidative stress, and heightened bone resorption. Inhibiting DNMT inhibitors (DNMTi) has shown effectiveness in preclinical animals by reversing abnormal methylation patterns and restoring bone mass. Additionally, DNA methylation profiles generated from peripheral blood exhibit significant concordance with bone tissue methylation, presenting prospective non-invasive biomarkers for OP diagnosis, prognosis, and therapy monitoring of OP. Incorporating epigenetic profiling into clinical practice could facilitate precision medicine strategies for OP, combining immune regulation with targeted DNA methylation therapy. This study emphasizes the relationship between DNA methylation and osteoimmunity, delineating innovative treatment targets and biomarker prospects to enhance OP therapy.